'Did You See That?'—The Role of Repetition and Enhancement on Lexical Bundle Processing in English Learning Materials. (21st October 2021) - Northbrook, Julian; Allen, David; Conklin, Kathy
Abstract: For second-language learners, the use of formulaic language can benefit processing. Previous studies have explored the development of a 'processing advantage' for lexical bundles and investigated whether learning materials can be optimized via repetition or enhancement in order to facilitate it. However, studies have tended to consider these factors in isolation, and little is understood about how repetition and enhancement interact as learning occurs. This is the focus of the current study. Japanese learners of English read a series of short stories repeating enhanced or un-enhanced, low-frequency lexical bundles. After each reading, participants performed a phrasal judgement task (PJT) including these lexical bundles, as well as control lexical bundles not presented in the story. Responses were faster to items repeated in the stories, and there was an initial benefit from input enhancement. A post-test indicated that students retained some knowledge of the lexical bundles from both the stories, as well as from items that only appeared in the PJTs. This study shows that including high-frequency lexical bundles in such texts is beneficial to learners.